2018
DOI: 10.2478/bile-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

AMMI and GGE Biplot for genotype × environment interaction: a medoid–based hierarchical cluster analysis approach for high–dimensional data

Abstract: The presence of genotype-environment interaction (GEI) influences production making the selection of cultivars in a complex process. The two most used methods to analyze GEI and evaluate genotypes are AMMI and GGE Biplot, being used for the analysis of multi environment trials data (MET). Despite their different approaches, both models complement each other in order to strengthen decision making. However, both models are based on biplots, consequently, biplot-based interpretation doesn't scale well beyond two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 25 publications
6
52
0
5
Order By: Relevance
“…Especially, E3 had the shortest vector as compared to the rest environments and recorded above average mean grain yield, therefore, it is the most ideal environment for the tested bread wheat genotypes. Similar results were reported by Golkari et al (2016) and Neisse et al (2018).…”
Section: Stability Analysis By Ammi Modelssupporting
confidence: 92%
“…Especially, E3 had the shortest vector as compared to the rest environments and recorded above average mean grain yield, therefore, it is the most ideal environment for the tested bread wheat genotypes. Similar results were reported by Golkari et al (2016) and Neisse et al (2018).…”
Section: Stability Analysis By Ammi Modelssupporting
confidence: 92%
“…The use of principal component analysis in biplots will minimize overlapping of variations so that the group determination can be more objective (Mattjik and Sumertajaya 2011; Leite and Oliveira 2015). Therefore, this analysis can facilitate the determination of characters with the same direction variance to the main characters (Kose et al 2018), especially when using the orthogonal polygonal grouping concept of the outlier object (Leite and Oliveira 2015; Neisse et al 2018). Based on this analysis,these five characters which have the same direction with the productivity can be as the best secondary character candidates in the selection The result of biplot analysis also showed that the maximum temperature of the leaves was the only character with a variance direction in contrast to the productivity group (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…In order to explain the phenotypic variations, it is highly dependent on the effect of the environments. Explaining this diversity is upwards sophisticated by the fact that all genotypes don't react in the same way as change in circles and the two environments do not have exactly the same conditions (Neisse et al, 2018). If the performance of genotypes changes in different location, then the interaction of the genotype location is an important factor in plant breeding strategies.…”
Section: Introductionmentioning
confidence: 99%